Life through Death in Rumi’s Story of the Boatman and the Grammarian: A Thematic and Symbolic Analysis - Halil Şimşek (Ankara Üniversitesi İlahiyat Fakültesi Dergisi)
The following studyexamines the story/parable of the Grammarian and the Boatman within the Mathnavīof Rumi. We have striven to provide an account of the allegorical aspect of thestory and the messages that Rumi attempted to convey. We demonstrated that theprimary objective of the story is to signify the Sufi concept of maḥv(self-effacement/annihilation) and prioritize it in the life of the Sufidisciple. We examined and analyzed how the theme of maḥv is presentedthrough an earthly experience, and explored the symbols Rumi, and the Sufis forthat matter, utilized in conveying their teachings. We have also drawnparallels with Qur’anic verses, prophetic teachings, and the teachings ofearlier Sufi masters. The Sufi epistemological approach, the experientialknowledge, has been the primary examination of our research, and we drewattention to how the Sufi masters imparted knowledge to their audience. Otherpoetic formulations of Rumi in various parts of Mathnavī have beenenlisted to elucidate the author’s mindset on the theory of knowledge. Similarattestations of other Sufi mystics have also been utilized in this survey andthe mutual objectives of other Sufis have been analyzed. We have striven tomaintain an analytical approach and provided an expository formulation of theSufis on the nature of epistemology.